Pemberdayaan Perempuan Desa Tempurejo terhadap Diversifikasi Potensi Produk Olahan Pisang melalui Pelatihan Produksi dan Penjualan - Iwan Wicaksono; Riska Rian Fauziah; Slamet Hariyadi; I Ketut Mahardika; Sutarto Sutarto (Yayasan Literasi Sains Indonesia, 2025)
Tempurejo Village in Jember Regency boasts abundant banana potential, considered one of the village's leading products. However, its utilization remains suboptimal. This community service research aims to empower women in Tempurejo Village, Jember, who are predominantly housewives, to increase family income through the diversification of processed banana products. Tempurejo Village has significant potential as a center for banana production and collection, but local processed banana products are still traditional, lack branding, and face limited marketing knowledge. Using a Participatory Rural Appraisal (PRA) approach, the activities were carried out through stages of team formation, objective formulation, stakeholder identification, needs analysis, problem prioritization, preparation, material implementation, and practical training. A total of 30 housewives were trained to produce economically valuable banana processed products such as crispy banana nuggets, molten bananas (pisang lumer), and banana toast (pisang roti tawar). Furthermore, the training also covered packaging skills, the creation of the